Diagnostic Value of Delayed Contrast-Enhanced Cardiac Computed Tomography for Detecting Left Atrial Appendage Thrombus in Patients With Atrial Fibrillation - Li, Xiang-Nan; Wang, Jing-Xi; Wei, Qing; Yu, Xian-Bo; Zhou, Yu-Tao; Ma, Xiao-Yan; Zhao, Na; Lu, Bin (Frontiers in Cardiovascular Medicine, 2022)
Background: Delayed enhancement cardiac CT is a reliable tool for the diagnosis of left atrial appendage thrombus but limited for scanning heterogeneity. Aims: To explore the improvement of the 1-minute and 3-minute delay phase at the diagnostic level to detect left atrial appendage thrombus, in order to set up a reasonable CT scanning scheme. Methods: A total of 6524 patients were continuously retrieved from January 2015 to September 2020 retrospectively. The patients had undergone Transesophageal echocardiography (TEE) and cardiac CT with complete period include the arterial enhancement phase, 1-min, and 3-min delay phase, TEE were used as the reference standard. The final study included 329 patients. Three experienced radiologists independently assessed each phase of the cardiac CT images for thrombus diagnosis. We explored the improvement of the diagnostic ability of different delayed contrast-enhanced phases for left atrial appendage thrombus detection. Multiple logistic regression analysis were used for further high-risk stratification to avoid an additional 1-minute delayed scan. Results: In total, 29 thrombosis were detected at TEE. For all cardiac CT phases, sensitivity and negative predictive were 100%. The specificity were 0.54, 0.93, 1.00 respectively; The positive predictive values (PPV) were 0.17, 0.57, 1.00 respectively; Area under curve (AUC) were 0.75, 0.95, 0.98 respectively. High risk factors that cannot be clearly diagnosed with 1-min delay phase included reduced cardiac function, increased CHA2DS2-VAScscore and left atrial enlargement. Compared with the arterial enhanced phase, increased radiation doses in the 1-min and 3-min delay phases were 1.7 ± 1.3 msv and 1.5 ± 0.8 msv. (mean ± standard deviation). Conclusion: Using TEE as the reference standard, early contrast-enhanced CT scanning with 1-min and 3-min delay is necessary for the diagnosis of left appendage thrombus, which could significantly improve the diagnostic efficiency. Patients with high-risk stratification are suitable for direct 3-min delayed scanning.